Analisa Keimanan Mahasiswa dalam Pembelajaran Pendidikan Agama Islam secara Daring: Perspektif Psikologi - Wira Yudha Nuswantoro; Handre Syahrul Fanani; Erwin Kusumastuti (Atta'dib Jurnal Pendidikan Agama Islam, 2021)
Islamic Religious Education is an important thing that needs to be taught to every student. By studying Islam, students should be able to become individuals who have noble morals, have a stand, and can be an example for others. In the current pandemic situation, it requires all learning to be carried out online, including learning Islamic Religious Education. This raises concerns for educators whether online learning can increase student faith. With these problems, research is needed to analyze the level of faith in online Islamic Religious Education from a psychological perspective. The study used qualitative data collection methods through questionnaires and in-depth interviews with 70 correspondents who were Industrial Engineering Students of UPN "Veteran" East Java. Correspondents will be given five questions regarding Islamic Religious Education learning which are also related to the indicator of faith from a psychological perspective. From the research, it was found that the total faith of the 70 correspondents was 83.2244898%. These results are quite good, but cannot reach maximum validity because only Allah SWT. Which can measure someone's faith with certainty.